Expert stakeholder perspectives on safe return to sport in high-performance snowsport: exploring current practices, challenges, and opportunities - Philippe, M.; Moritz, H.; Scherr, J.; Verhagen, E.; Bolling, C.; Spörri, J. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Careers in snowsports often have severe musculoskeletal injuries. 1 Accordingly, return to sport processes after injuries play critical roles in continuing athletes' careers. The aim of this study was to explore current practices, challenges and opportunities related to return to sport in snowsports.